Democratic Decision Making and the Psychology of Risk - Christiansen, Andreas; Hallsson, Bjørn (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2017)
In many cases, the public (or large parts of it) want to restrict an activity or technology that they believe to be dangerous, but that scientific experts believe to be safe. There is thus a tension between respecting the preferences of the people and making policy based on our best scientific knowledge. Deciding how to make policy in the light of this tension requires an understanding of why citizens sometimes disagree with the experts on what is risky and what is safe. In this paper, we examine two highly influential theories of how people form beliefs about risks: the theory that risk beliefs are errors caused by bounded rationality and the theory that such beliefs are part and parcel of people’s core value systems. We then discuss the implications of the psychological theories for questions regarding liberal-democratic decision making: (1) Should policy be responsive to the preferences of citizens in the domain of risk regulation? (2) What risk-regulation policies are legitimate? (3) How should liberal-democratic deliberation be structured?